MARKETING COMMUNICATION USED BY YOUNG ENTREPRENEURS IN THE EASTERN PART OF INDONESIA: THE USE OF SEMIOTIC ANALYSIS - Razak, Darmianti; Mursyid, Andi Miftahul Maulidil; Hakim, Fitriani (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This research illustrates how the discipline of semiotics can be utilized to investigate the hidden meanings that lie beneath marketing communication. The study of symbols and the underlying meanings that are connected to them is referred to as semiotics. Symbols can be in the form of written words or visual representations, and the study of semiotics focuses on both types of symbols. For this reason, and due to the fact that digital marketing makes extensive use of symbols and other promotion attributes in order to influence both brand awareness and brand image, semiotics is a very effective and efficient tool for interpreting digital marketing. This study will investigate the ways in which language and/or symbol influence consumer behavior with the end goal of determining how those factors contribute to the success of entrepreneurial endeavors. The study will investigate the ways in which language and/or symbol influence consumer behavior. In addition, the purpose of this study is to determine how young businesspeople in the eastern part of Indonesia can use semiotics as a tool to deliver marketing communication efforts to the audience that they have in mind. Not only that, but also this study will fill the gap of knowledge regarding the use of digital marketing and how it influences consumer particularly in the eastern part of Indonesia